ETIKA PENGENALAN NOTARIS YANG BERKEGIATAN DI PASAR MODAL PADA PAPAN NAMA NOTARIS DITINJAU DARI KODE ETIK NOTARIS - Gustian Pratiwi; Daly Erni (The Juris, 2021)
This study examines the appropriateness of making a notary nameplate who is active in the capital market in order to carry out his position. The research method in this thesis is normative juridical, namely by library research, with a statutory approach. type of descriptive research, which helps in strengthening hypotheses in order to help strengthen old theories or in formulating new theories. The data used is secondary data consisting of primary legal materials in the form of the notary position law, financial services authority regulations (OJK) and the Notary Code of Ethics (KEN), secondary legal materials in the form of journals and articles as well as supporting books on the position of a notary and tertiary legal materials. In the results of this study, it was found that there was an ethical violation if the notary listed on his name board that he was a capital market notary. In addition, it is also seen as less effective in supporting the notary profession which is an honorable profession that cannot promote itself (officium nobile). Building connections with fellow capital market supporting professions is recommended so that they can carry out activities in the capital market apart from being registered as a notary in the capital market.